Best Answer

Radical (3x) = radical(x) * radical(3).

Q: The expression radical 3x is equivalent to the expression x radical 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

3(x-y)

If you mean -3(x+10) then it is -3x-30

2(3x + 4) = 6x + 8 3(x - 5) = 3x - 15 6x + 8 - 3x + 15 = 3x + 23

3x+3-2x=3 x+3=3 x-0

6 radical 6

Related questions

3x + 3x + 3x = 3* (3x) = 9x

-9

3(x-y)

If you mean -3(x+10) then it is -3x-30

2(3x + 4) = 6x + 8 3(x - 5) = 3x - 15 6x + 8 - 3x + 15 = 3x + 23

2(3x + 4) = 6x + 8 3(x - 5) = 3x - 15 6x + 8 - 3x + 15 = 3x + 23

In a mathematical sense, 3x isn't an equation, but an expression. In this expression, 3 is a coefficnet.

when you say 3x, you mean that there are 3 x's. Multiplication implies repeated addition, so three x's added is x+x+x, which equals 3x.

3x+3-2x=3 x+3=3 x-0

3

6 radical 6

D.2√3